EVALUASI PROGRAM PENGEMBANGAN PROFESIONAL GURU MELALUI SUPERVISI AKADEMIK DI ERA REVOLUSI INDUSTRI 5.0 - Rusendra Ichwan; Ahmad Sukandar (Jurnal Manajemen Pendidikan, 2026)
Objective: This study examines the ineffectiveness of the Teacher Professional Development Program (PPG) through academic supervision in the era of the Industrial Revolution 5.0, where the digital competence of Indonesian teachers only reaches 35% due to conventional supervision methods. The main objectives include identifying the current academic supervision model, evaluating its effectiveness using the POAC framework, and providing recommendations for adaptive education management. Methods: This library research analyzed 138 journal articles from 2021-2026 through content analysis to explore trends in academic supervision and the integration of Society 5.0 technology. Results: Findings show that PPG evaluation only reaches 70% field application, 27% digital supervision, and 19% Industry 5.0 adoption. The stagnation of teachers' digital competence is caused by dependence on conventional approaches. Novelty: This study introduces the POAC-Society 5.0 synthesis for a blended supervision model, with a three-year roadmap targeting a teacher competency index of 85%. This approach is an original contribution to adapting education management in the digital era in Indonesia.